Efeitos de um programa de atividade física e do laser de baixa intensidade no fêmur de ratas osteopênicas - Renno, Ana Cláudia Muniz (2006)
Objective: The aim of this study was to investigate the effects of low-power laser therapy (LLLT), infrared 830 nm, used in two doses, on femora of ovariectomized (OVX) rats. Background data: Osteoporosis has recently been recognized as a major public health problem. Based on the stimulatory effects of LLLT on proliferation of bone cells, we hypothesized that LLLT would be efficient to improve bone mass in OVX rats. Methods: It was used 60 females animals, divided into 6 groups: sham-operated control (SC), OVX control (OC); sham-operated irradiated with the dose of 120 J.cm-2 (I120), OVX irradiated with the dose of 120 J.cm-2 (O120); sham-operated irradiated with the dose of 60 J.cm-2 (I60) and OVX irradiated with the dose of 60 J.cm-2(O60). Animals were operated at the age of 90 day-old. Laser irradiation initiated 8 weeks after operation and it was performed 3 times a week, during 2 months. Femora were submitted to a biomechanical test and to a physical properties evaluation. Results:Maximal load of O120 did not show difference when compared with SC and I120 and it was higher than the O60 group. Wet weight, dry weight and bone volume of O60 and O120 did not show any difference when compared with SC. Conclusion: The results of the present study indicate that LLLT had beneficial effects on established osteopenia in OVX rats, mainly at the dose of 120 J.cm-2. However, further studies are needed to investigate the effects of different parameters, wavelengths and sessions of applications on OVX rats.